Morphological stabilization and regression of carotid plaque following therapy with evolocumab in a high‐risk patient. Issue 6 (26th August 2020) - Aranzulla, Tiziana Claudia; Musumeci, Giuseppe
Abstract: Lipid‐lowering therapy is a mainstay for the management of coronary and carotid disease. Actually, progression of atherosclerosis and adverse events are reduced in proportion to the achieved levels of LDL cholesterol (LDL‐C). A 67‐year‐old patient underwent two hospitalizations 6 months apart due to acute coronary syndromes. In the first, PCI with drug‐eluting stents (DES) was performed to treat ulcerated stenoses in the left anterior descending artery. In the second, lipid‐rich critical disease was found on the right coronary artery and treated with PCI + DES. Later, carotid duplex ultra‐sonography (DU) was done due to some episodes of dizziness. It showed an 80% critical stenosis (peak systolic velocity, PSV 239 cm/s) of the left internal carotid artery (LICA) with high‐risk features (hypoechogenic and irregular plaque with "fluffy" components). In consideration of the plaque morphology and the unmet LDL‐C targets, evolocumab was added to the ongoing statin therapy. In the following months, we observed a parallel trend between carotid plaque regression and LDL‐C lowering. Initial plaque remodeling was seen after 5 months: the atheroma appeared fibrotic, with no more fluffy components. At 10 months, in conjunction with the achievement of LDL‐C goal (23 mg/dl), a fibrocalcific atheroma was observed; PSV, after an initial rise, fell to 229 cm/s. No further cardiovascular event occurred at 46 months. Last DUS showed a 60% fibrocalcific mid LICA stenosis with PSV of 180 cm/s. Our experience highlights the important role of proprotein convertase subtilisin kexin type 9 (PCSK9) inhibitors in promoting remodeling and hopefully regression of atherosclerotic plaques.